Invasive meningococcal disease in children and adults in a tertiary level hospital. Recent epidemiology and prognostic factors - Daniela Maturana Martínez; David Aguilera-Alonso; Julia García Mancebo; María Luisa Navarro; Teresa Hernández Sampelayo; Elena María Rincón López; Begoña Santiago-García; Jesús Saavedra-Lozano; Mar Santos; Emilia Cercenado (Elsevier, 2019)
Introduction: Invasive meningococcal disease (IMD) has a high morbidity and mortality in children and adults. The aim of this study was to describe the clinical and epidemiological characteristics of patients with IMD, to compare them among children and adults, and to determine prognostic factors and changes in epidemiology during a 14-year period. Methods: A retrospective study was conducted on patients admitted to a third level hospital with IMD between 2004 and 2017. An analysis was made of the clinical, epidemiological and microbiological data. Results: A total of 84 patients were diagnosed with IMD, of which 50 (59.5%) were children. Median age was 2 years (IQR 0.7-7.5) for children and 41.2 years (IQR 26.4-69.3) for adults. Diagnosis was bacteraemia in 47 patients (56%), meningitis in 24 (28.6%), and both in 13 (15.5%). Serogroup B (MenB) was the most common cause of IMD (40.5%), followed by serogroup C (MenC) in 15.5%, which was more common among adults (26.5% vs 8%, P = .022). Incidence rate decreased between 2004-2010 and 2011-2017, from 3.14 to 1.33 cases/100 000 emergencies attended in the study hospital (P < .001). Eighty-four percent of children had received ≥1 dose of vaccine against MenC, with none against MenB. Children had higher proportion of ICU admissions (78% vs 44.1%, P = .001). Mortality was slightly higher in adults (11.8% vs 2.0%, P = .153). Adverse outcomes (sequelae or mortality) were independently associated with intubation and thrombocytopenia, while disease severity with leukopenia and purpuric rash. Conclusions: IMD incidence has decreased in our setting, with MenB being the most common serogroup. The higher prevalence of MenC in adults was probably related to lower vaccination coverage. According to this study, thrombocytopenia, leukopenia, and purpuric rash were parameters associated with worse outcome. Resumen: Introducción: La enfermedad meningocócica invasiva (EMI) supone una causa importante de morbimortalidad en niños y adultos. Objetivo principal: describir las características clínicas y epidemiológicas de los pacientes con EMI. Objetivos secundarios: describir las diferencias entre niños y adultos, factores pronósticos y cambios epidemiológicos en los últimos 14 años. Métodos: Estudio retrospectivo realizado en un hospital terciario. Se incluyeron los pacientes diagnosticados de EMI entre 2004 y 2017, recogiéndose datos epidemiológicos, clínicos y microbiológicos. Resultados: Fueron diagnosticados 84 pacientes con EMI, 50 (59,5%) niños. Edad mediana en niños 2 años (RIC: 0,7-7,5) y adultos 41,2 años (RIC: 26,4-69,3). Bacteriemia en 47 casos (56%), meningitis en 24 (28,6%) y ambas en 13 (15,5%). Predominio del serogrupo B (MenB), en el 40,5%, seguido del serogrupo C (MenC), en el 15,5%, con mayor proporción de MenC en adultos (26,5 vs. 8%; p = 0,022). Disminución en la incidencia de 2004-2010 a 2011-2017, pasando de 3,14 a 1,33 casos/100.000 urgencias en el centro de estudio (p < 0,001). El 84% de los niños había recibido ≥ 1 dosis de vacuna frente a MenC, ninguno frente a MenB. Mayor proporción de ingreso en UCI en niños (78 vs. 44,1%; p = 0,001). Tendencia a mayor letalidad en adultos (11,8 vs. 2%; p = 0,153). La intubación y la trombocitopenia fueron factores de riesgo independientes de desenlace adverso, y la leucopenia y el exantema purpúrico de gravedad. Conclusiones: Se objetivó un descenso en la incidencia de EMI, siendo MenB el mayoritario. El mayor porcentaje de MenC en adultos probablemente esté relacionado con una menor cobertura vacunal. La trombocitopenia, la leucopenia y el exantema purpúrico fueron factores de riesgo relacionados con peor pronóstico.